VP46 Cost Analysis Of Popliteal Aneurysm Management. (2017) - Pinget, Christophe; Allain, Elisabeth; Saucy, François
Abstract : INTRODUCTION: Popliteal artery aneurysm (PAA) is the most common peripheral arterial aneurysm and the second most common aneurysm after abdominal aortic aneurysm (AAA). It presents a risk of occlusion, which may lead to acute ischemia and leg amputation. To prevent these risks, asymptomatic PAA >2cm and symptomatic PAA must be treated. Although open PPA repair (OPAR) is still the gold standard, endovascular PAA repair (EPAR) is increasingly used to manage PAA. The objective of this study is to compare the cost of these two medical procedures from the hospital perspective. METHODS: Data were retrieved from the administrative database of Lausanne University Hospital (CHUV – Switzerland). Based on diagnostic codes and medical procedure codes, we selected all patients who underwent OPAR or EPAR between 2011 and 2015. Patient's age, length of stay and cost were compared between both groups using Student t-test. RESULTS: We included seventy-three patient stays (OPAR forty and EPAR thirty-three). Gender balance was identical between groups (97 percent of male), but age was statistically significantly different (OPAR 67.5, EPAR 73, p = .04). EPAR induced shorter mean length of stay (5.1 days versus 11.7 days, p = .0000) and lower mean global cost (CHF 16, 555 versus CHF23, 514, p = .0085). Cost of procedure amounted to CHF 9, 536 for OPAR versus CHF 3, 848 for EPAR, medical supply and implants amounted to CHF 1, 284 for OPAR versus CHF 7, 041 for EPAR and other costs of hospital stay amounted to CHF 12, 694 for OPAR versus CHF 5, 666 for EPAR. (CHF 1.00 = USD1.00 = EURO 0.93) CONCLUSIONS: With higher patency rate, OPAR is still associated with better medical outcomes than EPAR. But EPAR is significantly less costly than OPAR. Implant cost of EPAR is more than offset by longer length of stay and operating time of OPAR.